2007
DOI: 10.1007/s10549-007-9505-z
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells in breast cancer patients

Abstract: Our findings lead to the tumor, as source of angiogenic chemokines, is most important for recruiting CD34(+)FLK-1(+ )EPCs during breast cancer development. Therefore circulating endothelial progenitor cells may work as a new diagnostic tool in the screening and diagnosis of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
1
17
0
2
Order By: Relevance
“…In addition, we observed a significant correlation between the modulation of CD31 þ /VEGFR-2 þ and the likelihood of obtaining a clinical response, in that patients who responded to treatment did not experience an increase of this sub-population of CEC. CD31 þ /VEGFR-2 þ cells are crucial in the neovascularisation process and have recently been shown to be elevated in breast cancer patients to significantly correlate with tumour size and to rapidly decline after removal of the tumour, suggesting a possible induction by tumour-driven angiogenic stimuli (Richter-Ehrenstein et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed a significant correlation between the modulation of CD31 þ /VEGFR-2 þ and the likelihood of obtaining a clinical response, in that patients who responded to treatment did not experience an increase of this sub-population of CEC. CD31 þ /VEGFR-2 þ cells are crucial in the neovascularisation process and have recently been shown to be elevated in breast cancer patients to significantly correlate with tumour size and to rapidly decline after removal of the tumour, suggesting a possible induction by tumour-driven angiogenic stimuli (Richter-Ehrenstein et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…EPCs have a high proliferation potential and have been found to be a potential marker for neovascularisation and for the response to antiangiogenic therapies [4,5,10,13,14]. The role of EPCs in solid malignancies is less well studied than that of CECs.…”
Section: Discussionmentioning
confidence: 99%
“…Their conclusion was that since the mobilization of EPCs could contribute to tumor neovascularisation, early antiangiogenic therapy in combination with chemotherapy could be beneficial for successful treatment. Another recent study found elevated levels of EPCs in patients with breast cancer before therapy with a rapid decline after tumor excision [14]. Willett et al [15] investigated possible surrogate markers for antiangiogenic therapy with the vascular endothelial growth factor specific antibody bevacizumab in five rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies that only used FACS technique have been conducted to reveal the dynamics of CEPCs in various cancer types such as lung cancer [22,[52][53][54], malignant glioma [20,55,56], HCC [21,57], breast cancer [58,59], head and neck cancer [60], ovarian cancer [61][62][63], cervical cancer [63], colorectal cancer [64], prostate cancer [65], renal cell carcinoma (RCC) [66,67], osteosarcoma [68], and multiple myeloma [69] (Table 1). However, inconclusive and controversial results were obtained; although in most studies, a significantly higher EPCs concentration was observed in the peripheral blood of cancer patients.…”
Section: Circulating Levels Of Epcs In Cancer Patientsmentioning
confidence: 99%